2005
DOI: 10.1152/ajpgi.00381.2004
|View full text |Cite
|
Sign up to set email alerts
|

Na+/Ca2+ exchange regulates Ca2+-dependent duodenal mucosal ion transport and HCO3 secretion in mice

Abstract: Ca 2ϩ exchange regulates Ca 2ϩ -dependent duodenal mucosal ion transport and HCO 3 Ϫ secretion in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Although NCX expression and function have been demonstrated in intestinal epithelial cells (12) and in pancreatic ␤-islet cells (12), little is known about NCX in human pancreatic adenocarcinoma cells (22). Here, we demonstrated that both the mRNA transcript and protein of NCX1 are expressed in pancreatic cancer cells (Fig.…”
Section: Expression Of Ncx and Trpc Channel In Pancreatic Cancer Cellsmentioning
confidence: 60%
“…Although NCX expression and function have been demonstrated in intestinal epithelial cells (12) and in pancreatic ␤-islet cells (12), little is known about NCX in human pancreatic adenocarcinoma cells (22). Here, we demonstrated that both the mRNA transcript and protein of NCX1 are expressed in pancreatic cancer cells (Fig.…”
Section: Expression Of Ncx and Trpc Channel In Pancreatic Cancer Cellsmentioning
confidence: 60%
“…NCX1 is ubiquitously expressed in mammalian heart and brain tissue, where it is responsible for calcium homeostasis [43], although it is also widely expressed in other tissues [4,40]. NCX1 participates in essential processes such as balancing calcium ion concentrations by regulating duodenal mucosal ion transport and HCO3-secretion and controlling calcium ion homeostasis [16]. NCX1 also participates in cardiac muscle relaxation and in the maintenance of calcium concentration in the sarcoplasmic reticulum in cardiac cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial HCO 3 Ϫ and Cl Ϫ secretion is mainly under the control of cyclic AMP and Ca 2ϩ signaling, which may interact and cross-talk to regulate epithelial ion transports (25,42,53,54). Previous studies demonstrated that most well known secretagogues, such as forskolin, ACh, 5-HT, and PGE 2 , usually stimulate intestinal HCO 3 Ϫ and Cl Ϫ secretion in parallel (20,42,55,56). It is not known, however, whether epithelial HCO 3 Ϫ and Cl Ϫ secretion has to occur in parallel and whether they are regulated by the same or different signaling/mechanisms.…”
Section: Diated Intestinal Transepithelial Hcomentioning
confidence: 99%